APPLYING SERVQUAL MODEL TO MEASURE ONLINE CUSTOMER SATISFACTION IN PACKAGE DELIVERY SERVICES - Nusrat HAFIZ; A. S. A. FERDOUS ALAM (Studia Universitatis Babeş-Bolyai Negotia, 2016)
Online customer is a person or association that purchases goods from a retail store via internet. This online purchasing is facilitated by companies that deliver shipping parcels, known as package delivery companies. The service quality is measured by the difference between customers’ expectations towards a service and their actual experience from that service. The objective of the study is to explore the correlation of online customer satisfaction with service quality in the package delivery industry using quality management framework SERVQUAL. Quantitative data on customer satisfaction levels divulged from questionnaires were scrutinized against service quality factors, which was later replaced in the service quality model using a five-point Likert scale and conducting simple regression. The result of the study found positive impact of reliability, assurance and empathy dimensions of service quality model on online customers’ satisfaction level pertaining to package delivery companies, with overall dominance of reliability dimension. The study adds value to the untapped sector of package delivery service, a critical backbone of e-commerce. The findings can be applicable for any e-commerce entrepreneurs in order to enhance optimum customer management efficiency by focusing on imperative dimensions of service quality model and perking up customer satisfaction.